Dosimetric effects of the Smit sleeve on high-dose-rate brachytherapy tandem and ovoids plans for patients with locally advanced cervical cancer - Mehta, Shahil (J Contemp Brachytherapy, 2019)
PURPOSE: Smit sleeves are used to facilitate insertion of the intrauterine tandem during brachytherapy for cervical cancer. When a tandem and ovoids system is used the base of the Smit sleeve displaces the ovoids distally. The dosimetric impact of this displacement is not known. Herein we performed a dosimetric analysis to quantify this impact on the integral dose and dose delivered to the organs at risk (OARs). MATERIAL AND METHODS: Eleven high-dose-rate brachytherapy plans in which a Smit sleeve was used with a tandem and ovoids were reviewed. A second set of plans was generated modifying the position of the ovoids to simulate absence of the Smit sleeve. The high-risk clinical tumor volume (HR-CTV) dose coverage was maintained the same for both sets of plans by appropriately rescaling the dwell times of the simulated plan. The mean integral dose, D(2cc) to the OARs (bladder, bowel, sigmoid and rectum) and the ICRU rectum point dose were compared between the original and modified plans using a paired two-sample t-test. RESULTS: Simulating removal of the Smit sleeve was associated with an average reduction in the mean integral dose of 6.1% (p < 0.001) and an average reduction of 10.9% (p = 0.004) to the rectal D(2cc). Doses to the remaining OARs decreased to a lesser magnitude with only that of the sigmoid being statistically significant. CONCLUSIONS: The use of a Smit sleeve with a tandem and ovoids system could lead to the delivery of a higher mean integral dose to achieve similar HR-CTV coverage. In addition, it could increase the dose to surrounding OARs, primarily the rectum. The clinical significance of these findings is unknown, but the potential dosimetric impact of using a Smit sleeve should be taken into consideration during the planning when this device is used.